Anatomy and Cellular Constituents of the Human Olfactory Mucosa: A Review - Chen, C. Russell; Kachramanoglou, Carolina; Li, Daqing; Andrews, Peter; Choi, David (Journal of Neurological Surgery Part B: Skull Base, 2014)
Studies using animal models have recently suggested that the olfactory mucosa may be a source of cells capable of stimulating and contributing to complex neurologic regeneration. Several groups have already transplanted cell derivatives from the olfactory mucosa into injury models, and the results so far have been promising. To fully appreciate the meaning of these experiments, a better understanding of the cellular biology and physiology of the olfactory system is necessary. It is therefore of utmost importance for us to first identify and understand its constituents.
Keywords: olfactory mucosa; olfactory system; olfactory ensheathing cells; spinal cord repair